2013
DOI: 10.1589/jpts.25.287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Application Direction of Kinesio Taping on Isometric Muscle Strength of the Wrist and Fingers of Healthy Adults — A Pilot Study

Abstract: Abstract.[Purpose] The purposes of this study were to investigate the immediate and delayed effects of two directions of Kinesio taping (KT) on maximal isometric strength of the wrist and finger muscles of healthy adults and compare their differences.[Subjects] Nineteen healthy junior college students participated in this study. [Methods] The inhibition and facilitation KT techniques were separately used to tape on the dominant and non-dominant forearms of the participants, respectively. Maximal isometric st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 17 publications
1
24
2
1
Order By: Relevance
“…However, results of the present study were in contrast to studies by Kuo et al [20], Mohammadi et al [10] and Thiago et al [21] who observed positive effects of kinesio taping on hand grip strength. Kuo et al [20] used facilitation and inhibition techniques of kinesio taping on maximal isometric strength of wrist and finger muscles.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, results of the present study were in contrast to studies by Kuo et al [20], Mohammadi et al [10] and Thiago et al [21] who observed positive effects of kinesio taping on hand grip strength. Kuo et al [20] used facilitation and inhibition techniques of kinesio taping on maximal isometric strength of wrist and finger muscles.…”
Section: Resultscontrasting
confidence: 99%
“…Kuo et al [20] used facilitation and inhibition techniques of kinesio taping on maximal isometric strength of wrist and finger muscles. They concluded that the applied direction of taping may have different effects on isometric hand grip strength.…”
Section: Resultsmentioning
confidence: 99%
“…Recent observations have suggested that the strength performance might be muscle-dependent due to the different muscle groups covered by KT. 10 The reason may be that the area covered by KT at different target muscles could be affected varyingly by the tactile stimulation or mechanical assistance afforded by the tape. Furthermore, muscles can be functionally categorized as either phasic or tonic.…”
Section: Discussionmentioning
confidence: 99%
“…9 Little is known about the isokinetic muscle strength of phasic muscles, e.g., wrist extensors and flexors, after applying the KT. 10 In highly skilled adult tennis players, significantly greater isokinetic strength was observed for the flexion and extension of dominant arm wrist. 11 More importantly, a recent electromyographic study has indicated that the wrist extensor and flexor muscles play an important role in gripping during the procedure of holding the racket in an extended tennis or badminton match.…”
Section: Introductionmentioning
confidence: 99%
“…I-shape kinesio and rigid taping was done in group A and B respectively for the wrist extensor muscles in the present study. Specific taping resulted in greater tactile stimulation of the wrist extensors and inhibition of other muscles 20 . Improvement in strength of the wrist extensors placed the wrist and hand in a mechanical advantage position thereby improving the pinch strength in the subjects.…”
Section: Discussionmentioning
confidence: 99%